Undergraduate and Early Postgraduate Training in Intensive Care Medicine - Cordeiro, Nuno Almeida; Martins, António (Journal of the Portuguese Society of Anesthesiology, 2019)
Recognized in the United States of America as an autonomous medical specialty in the eighties, Intensive Care Medicine as ever since acquired an increasingly relevant role in inhospital care. However, such development as a specialty has not been followed by a proportional one in the undergraduate training of medical students. Consequently, medical students and junior doctors lack competencies both in the care of the acutely ill patient and in emergency. In this study, we aim to non-systematically review the most recent literature on undergraduate and early postgraduate training in Intensive Care Medicine. This review was performed using PubMed, Science Direct and Google Scholar databases, focusing on the literature published over the last 18 years. The lack of basic practical and theoretical competencies in Intensive Care Medicine among medical students and junior doctors can be explained by historical and organizational factors inherent to this field of medical knowledge. Undergraduate training in acute care medicine must start early and be continued throughout medical school. Intensive Care Medicine must battle for its inclusion in current undergraduate curricula and the Portuguese reality should be assessed in a way to define a national standard-curriculum of required competencies.